Comparison of Selected Crystal Structures of Rod-like Molecules with Acid and Ester Terminal Groups - Peter Zugenmaier (Crystals)
The crystal structures of rod-like molecules with nitro-biphenyl or nitro-phenyl end groups and attached n-alkyl units with terminal acid or ester groups are determined by single crystal analysis and their arrangements are compared. The molecules are linked by head-to-tail arrangements and form strings. They point in a single or two different directions and are placed side by side to create the crystal structure. Some of the space groups of the structures can only be determined by a statistical routine because strongly disordered structures prevent the use of extinction methods, since many extinction violations occur for monoclinic and orthorhombic unit cells. An agreement between experimental and calculated X-ray reflection intensities serves as proof of the correctness of the method as well as a test of the existence of an inversion center. The single crystals are grown in solution with ethanol, isopropanol, DMAc, and toluene as solvents. Cocrystals are formed in DMAc solutions by the dissolved acid compounds. The two-molecule asymmetric unit of the acid compound is reduced to a one-molecule asymmetric unit with one DMAc included which forms a hydrogen bond with the acid group of the biphenyl molecule. These changes alter the hydrogen bonding scheme along a string. Some structural similarities as the head-to-tail arrangement in the strings are maintained between the terminal acid and ester compounds despite disordered ester groups in the compounds and the ester molecules themselves at ambient temperature.